Predictable anthropogenic food subsidies, density‐dependence and socio‐economic factors influence breeding investment in a generalist seabird. (23rd October 2017) - Real, Enric; Oro, Daniel; Martínez‐Abraín, Alejandro; Igual, José Manuel; Bertolero, Albert; Bosch, Marc; Tavecchia, Giacomo
Abstract : Recent European policies on the ban of fishing discards and the closure of open‐air landfills are expected to reduce predictable and abundant food resources for generalist seabirds. In order to forecast the consequences of this reduction on seabird breeding investment it is important to understand whether diverse anthropogenic foraging resources act synergistically or not and whether their influence is mediated by density‐dependent mechanisms. To assess these effects at large spatio‐temporal scale, we measured mean egg volume as a proxy of breeding investment in ca 5000 three‐egg clutches of the yellow‐legged gull Larus michahellis from 20 colonies of the Western Mediterranean, located both along European and African coasts. In European gull colonies, egg volume increased with the availability of fishing discards and landfills in the vicinity of the colony. However, the landfill effect was weaker than the effect of fishing discards, probably due to the lower quality of waste as food for gulls. In contrast, none of the anthropogenic food subsidies influenced egg volume in African colonies, likely due to socio‐economic differences (i.e. a much lower availability and predictability of both discards and waste food. Finally, results showed that the positive association between fishing discards and open‐air landfills on egg volume was mediated by negative density‐dependent mechanisms probably related to an increase in competition for food.